2009
DOI: 10.1103/physrevlett.102.045008
|View full text |Cite
|
Sign up to set email alerts
|

Hot-Electron Temperature and Laser-Light Absorption in Fast Ignition

Abstract: Experimental data [F. N. Beg, Phys. Plasmas 4, 447 (1997)10.1063/1.872103] indicate that for intense short-pulse laser-solid interactions at intensities up to 5 x 10(18) W cm(-2) the hot-electron temperature proportional, variant(Ilambda(2)) (1/3). A fully relativistic analytic model based on energy and momentum conservation laws for the laser interaction with an overdense plasma is presented here. A general formula for the hot-electron temperature is found that closely agrees with the experimental scaling ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
128
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 186 publications
(141 citation statements)
references
References 8 publications
13
128
0
Order By: Relevance
“…14MeV, which can be attributed to the fact that the electrons only interact with the laser pulse during a fraction of the laser cycle before being accelerated forward beyond the laser penetration region due to the relatively short preplasma scale-length employed in our simulation 41 .…”
Section: Resultsmentioning
confidence: 99%
“…14MeV, which can be attributed to the fact that the electrons only interact with the laser pulse during a fraction of the laser cycle before being accelerated forward beyond the laser penetration region due to the relatively short preplasma scale-length employed in our simulation 41 .…”
Section: Resultsmentioning
confidence: 99%
“…However, it gives electron energies well over the desired values around 2 MeV for the laser intensities typical of the FI regime (>10 20 Wcm −2 ). Chrisman et al (Chrisman et al 2008), Haines et al (Haines et al 2009) and Kluge et al (Kluge et al 2011) have recently reported scaling laws that provide electron energies lower than those obtained by the ponderomotive scaling and of the same order than those predicted by the Beg's law. In principle, this is very favourable for FI because the optimal electron range is about 1.2 g/cm 2 (Atzeni 1999), which corresponds to an electron energy lower than 2 MeV ) and a laser intensity about 2.4×10 20 Wcm −2 assuming the Beg's scaling.…”
Section: Ignition Energies Of Divergent Electron Beams With An Assumementioning
confidence: 99%
“…This electron population can often be characterized by a so-called "slope temperature" approximately given by the "ponderomotive energy" kT p kT p = m e c 2 1 + Iλ 2 [ W µm 2 cm 2 ] 1.37 * 10 18 − 1 (1) where m e is the electron mass, c is the speed of light, and λ is the laser wavelength. This scaling has been the subject of experimental 10,17 , computational 9 , and theoretical 18 efforts.…”
Section: Introductionmentioning
confidence: 99%